MIMO Antenna with Notches for UWB System (MANUS) - Shahid Basir; Khurram Saleem Alimgeer; Sajjad A Ghauri; Moazam Maqsood; Mubashar Sarfraz; Md Yeakub Ali (International Journal of Antennas and Propagation)
In this paper, a trinotch band MIMO antenna is designed for upper and lower WLAN (5.1 GHz, 5.5 GHz) i.e., (802.11a/g/n/ac/ax) and satellite X-band (8.5 GHz). The placement of closely found notches at 5.1 GHz and 5.5 GHz is addressed by taking advantage from the placement of the same notch elements at appropriate distances from each other, to split single resonance into biresonances. Similarly, the third notch is produced at 8.5 GHz via a U-shaped slot added in the antenna. 2x1-MIMO antenna with notch bands is expected with better isolation by analysis of co-configurations and cross-configurations.